Oxidized Regenerated Cellulose Mimicking a Retained Laparotomy Sponge - Lauren E. Karnolt; Andrea L. Buras; Thomas J. Rutherford; Matthew L. Anderson (Case Reports in Surgery)
Oxidized regenerated cellulose (ORC) is an absorbable hemostat commonly used during gynecologic surgery. We present a case in which ORC was used in a patient undergoing posterior pelvic exenteration with ureteroneocystostomy for excision of a malignant pelvic mass. At the conclusion of these procedures, the laparotomy pad count was reported as incomplete likely due to the large number of laparotomy pads used and changes in nursing staff. Abdominal radiographs were obtained to verify no pads were retained in the abdominal cavity. These identified a poorly defined radiolucency deep in the patient’s pelvis, requiring the surgical incision be reopened. Upon reexploration, no evidence of a retained surgical sponge could be identified. However, ORC was identified at the site of the radiolucency in question. Radiographs of this material, once removed, confirmed its radiolucent appearance. This experience clearly demonstrates that oxidized regenerated cellulose can mimic a retained surgical sponge on intraoperative radiographs. Dissemination of this knowledge will hopefully help to avoid radiographic misidentification of ORC in the perioperative window and minimizing the risk of unnecessary surgical interventions in the future.